PERAN NCB INTERPOL INDONESIA DALAM MENANGANI KASUS TRANSNATIONAL INTERNET FRAUD TAHUN 2011-2014 - Rakhmadani, Herweningtyas; Windiani, Reni; Basith Dir, Andi Akhmad (Journal of International Relations, 2016)
Indonesia is one among countries that has a growing rate of internet users.As any other country in the world, various activities in Indonesia are held inthe internet, such as communication. Despite its positive side, internet has anegative side that allows criminals to commit crimes within itself, such asfraud. This kind of crime is executed by the criminal by deceiving its potentialvictim with false information in order to fulfill its personal gains through thevery function of the internet, communication channel. The condition will getworse as the crime is undertaken transcending national boundary whichmake it more difficult for law enforcement agency to solve regarding thedifference of jurisdiction. To deal with the case, Indonesia has been in aninternational police cooperation called Interpol and works through itsNational Central Bureau, NCB Interpol, in Indonesia. This research aims toknow the role of NCB Interpol Indonesia in handling transnational internetfraud case and to analyze the efficiency of it. This research is descriptiveanalytical which employs qualitative method and theory of internationalorganization with liberalism paradigm to analyze the data collected throughliterature studies, documentation, and interview as well. The result showsthat NCB Interpol Indonesia has the role as a facilitator of the two parties,Indonesia and Interpol, and is efficient enough in the field.